Polycystic ovary syndrome and prolactin - Coyotupa, Juan (2015)
In a series of 2,344 patients with polycystic ovarian syndrome diagnosed by ultrasound, plasma prolactin was determined and was found in PCOS prevalence of 15% Hyperprolactinaemia. In a group of 855 patients with hyperprolactinemia polycystic ovary syndrome was valued by ultrasound, finding polycystic ovary syndrome in 42% of patients with hyperprolactinemia.